A case–control study of current psychological well‐being and weight‐teasing history in young adults with and without bowel conditions. Issue 1 (6th January 2014) - Quick, V.; McWilliams, R.; Byrd‐Bredbenner, C.
Abstract Background The present study aimed to determine whether psychological well‐being and weight‐teasing history of young adults with bowel conditions (i.e. coeliac disease, inflammatory bowel diseases and irritable bowel syndrome) differed from those without bowel conditions. Methods Young adults (aged 18–26 years) completed an online survey that collected demographic information and assessed psychological well‐being (mentally and physically unhealthy days, self‐esteem, and depression, anxiety and obsessive compulsive disorder severity) and weight‐teasing history (Perception of Teasing Scale). Each bowel condition participant (cases = 135) was matched to four healthy participants (controls = 504) based on sex and body mass index (BMI) (±0.50 BMI units). Conditional logistic regression analyses were conducted and odds ratios (OR) and 95% confidence intervals (CI) were presented for all measures and demographics. Results Cases were significantly more likely to have poorer overall psychological well‐being. Specifically, cases were significantly (P ≤ 0.05) more likely to have more mentally and physical unhealthy days, depression, anxiety, and obsessive compulsive disorder symptoms than controls. Cases were also significantly more likely to recall being weight teased as a child (P = 0.02, OR = 1.26, 95% CI = 1.04–1.53) and being more upset from the weight‐teasing insults (P = 0.006, OR = 1.19, 95% CI = 1.05–1.35) than controls. Cases were also more than 1.5 times more likely to be made fun of (P = 0.03, OR = 1.63, 95% CI = 1.09–2.43) or laughed at (P = 0.01, OR = 1.77, 95% CI = 1.15–2.73) because of their weight than controls. Conclusions The findings of the present study suggest that healthcare providers should monitor the psychological well‐being of young adults with bowel conditions and incorporate opportunities for them to develop skills and strategies for coping.